The Modelling Of Tyre Rotation Behaviour With Tyre Pressure Monitoring System - Goh, Yik Choong (2017)
The number of motorized vehicles is rapidly increasing in the technology driven countries, and led to the dramatic increase in road accident. The causes of accidents can be categorized into three major factors which are road environmental condition, human behaviour, and vehicle defects. The vehicle defects are the only parameter that is controllable when compared with to other two factors. Statistics show that the tyre and wheels-related from motorcycles is the critical reason and major contributor to road death accident. Therefore, there is the necessity to build a system that is able to monitor the on-road tyre condition. Several existing monitoring systems are available, but each has its own advantages and disadvantages based on the application’s limitation. For example, the important parameter such as pneumatic pressure captured from the tyre is not in real-time, thus it may become worst when there is air leakage. Besides that, tyre rotation behaviour such as acceleration, deceleration and sharp brake condition is not considered which may tend to build up heat. Especially in the countries on the equator which have warm road pavement throughout the daytime. In addition, the placement of transceiver for wireless communication need to determine in order to avoid misinterpretation on the wrong/delayed result captured. The research objective is to develop a monitoring system that combines the advantages of direct and indirect measurement system in order to overcome the problem as discussed. The system needs to capture the real-time pressure level on running tyre and provide calculations on the total distance travelled by the vehicle through algorithms from investigation of tyre rotation behaviour. Apart from that, the power level parameter was studied through the received signal strength index (RSSI) calibration for transmission quality purposes. The system consist of two parts which are the transmitter module and receiver module. The transmitter module is built from combination of hardware such as microcontroller, bluetooth module and sensing devices which sat on the tyre rim to acquire tyre condition. Whereas, the receiver module is responsible to collect and analyze information from the transmitter module and provide a feedback whenever an abnormal tyre condition occurred. Several experiments were conducted, the result shows that the placement of transceiver can be justified with consistent RSSI at -70 dBm from different tyre rotation speed and different transmitter’s directions with the same displacement. The result also shows that the performance of tyre rotation behaviour is able to identify and provide the estimation of distance travelled by the vehicle with evidence support from distance travel calculation. Lastly, the pneumatic pressure level inside the tyre was captured and the result accuracy is further ensured with reversed engineering method with ± 20 kpa from project tolerance. Overall, the research work is able to capture the real-time pressure level on running tyre, provide calculation on total distance travelled based on tyre rotation cycle and position the transceiver based on the power level parameter to ensure the transmission quality.